2019
DOI: 10.1136/bmjopen-2019-031226
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Labour Inspection Authority’s regulatory tools for work environment and employee health: study protocol for a cluster-randomised controlled trial among Norwegian home-care workers

Abstract: IntroductionThere is a need to evaluate whether, and to what degree, labour inspections or other regulatory tools have the desired effects on psychosocial, organisational and mechanical work environment, and employee health. The Norwegian Labour Inspection Authority (NLIA) uses different tools and strategies to enforce compliance with occupational safety and health (OSH) legislation. The aim of the present study is to evaluate the effects of labour inspections and other regulatory tools employed by the NLIA. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…The study is part of a larger project, and a full description can be found in the published protocol. 22 In addition, we conducted a process evaluation. 23 This evaluated, using questionnaires, whether the interventions had been conducted as planned.…”
Section: Design and Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The study is part of a larger project, and a full description can be found in the published protocol. 22 In addition, we conducted a process evaluation. 23 This evaluated, using questionnaires, whether the interventions had been conducted as planned.…”
Section: Design and Methodsmentioning
confidence: 99%
“…This range was chosen to reduce intracluster variability and thus reduce the needed sample size. 22 Ineligible municipalities were municipalities that had recently, in 2017–2018, had labour inspections. Based on sample size calculations (see protocol 22 ), 132 of the 187 eligible municipalities were randomly assigned to one of four trial arms.…”
Section: Design and Methodsmentioning
confidence: 99%
See 3 more Smart Citations